2020
DOI: 10.21873/invivo.12082
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-A Is Associated With the Degree of TILs and PD-L1 Expression in Primary Breast Cancer

Abstract: Background/Aim: Vascular endothelial growth factor-A (VEGF-A), an important angiogenic factor, has been reported to effect cancer growth and development. Recent reports indicated that anti-VEGF therapy has an important effect of enhancing anti-tumor immunity in various cancers. In the current study, we investigated the relationship between VEGF-A expression and immunological factors, including programmed cell death ligand 1 (PD-L1) and the degrees of stromal tumor-infiltrating lymphocytes (TILs) in breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Hypoxia-mediated angiogenesis is associated with immune tolerance [ 86 ]. Hypoxia induces expression of VEGF, which inhibits dendritic cell maturation [ 87 , 88 ]; VEGF in turn enhances PD-L1 expression in dendritic cells, downregulating T cell function [ 89 91 ]. In addition, CD47 expression is related to HIF1A target VEGF.…”
Section: Hypoxia Contributes To Tumor Immune Escapementioning
confidence: 99%
“…Hypoxia-mediated angiogenesis is associated with immune tolerance [ 86 ]. Hypoxia induces expression of VEGF, which inhibits dendritic cell maturation [ 87 , 88 ]; VEGF in turn enhances PD-L1 expression in dendritic cells, downregulating T cell function [ 89 91 ]. In addition, CD47 expression is related to HIF1A target VEGF.…”
Section: Hypoxia Contributes To Tumor Immune Escapementioning
confidence: 99%
“…Previously, we reported that TIL scoring based on FDG PET/CT was related to pCR (37), and scoring the CD8/FOXP3 ratio might predict a pCR more accurately. PD-L1 is expressed on cancer cells and tumor-infiltrating macrophages by IFN-γ and suppresses VEGF expression and T-cell activity via the PD-1/PD-L1 pathway (38). Immune checkpoint inhibitors that block the PD-1/PD-L1 pathway have been demonstrated to improve progression-free survival and the pCR rate following neoadjuvant chemotherapy administered for TNBC (30,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that high expression levels of HSP90 (HSP90α and HSP90β) increase the likelihood of recurrence and distant metastases in triple negative and ER+/HER2-breast cancer, and are associated with higher mortality [69]. Overexpression of HSP90 in human breast cancer cells has been linked to enhanced cell proliferation [42] and metastasis, [70] as well as to short OS and aggressive clinicopathological characteristics, such as high clinical stage, large tumors, and lymph node involvement [71]. Lin et al reported that elevated HSP90AB1 expression was linked to a better overall survival of ER-and Basal-like breast cancer patients [55].…”
Section: Discussionmentioning
confidence: 99%